Radiation-Induced Hypomethylation Triggers Urokinase Plasminogen Activator Transcription in Meningioma Cells - Kiran Kumar Velpula; Venkateswara Rao Gogineni; Arun Kumar Nalla; Dzung H. Dinh; Jasti S. Rao (Neoplasia: An International Journal for Oncology Research, 2013)
Our previous studies have shown the role of radiation-induced urokinase plasminogen activator (uPA) expression in the progression of meningioma. In the present study, we investigated whether modulation of DNA methylation profiles could regulate uPA expression. Initially, radiation treatment was found to induce hypomethylation in meningioma cells with a decrease in DNA (cytosine-5)-methyltransferase 1 (DNMT1) and methyl-CpG binding domain protein (MBD) expression. However, oxidative damage by H2O2 or pretreatment of irradiated cells with N-acetyl cysteine (NAC) did not show any influence on these proteins, thereby indicating a radiation-specific change in the methylation patterns among meningioma cells. Further, we identified that hypomethylation is coupled to an increase in uPA expression in these cells. Azacytidine treatment induced a dose-dependent surge of uPA expression, whereas pre-treatment with sodium butyrate inhibited radiation-induced uPA expression, which complemented our prior results. Methylation-specific polymerase chain reaction on bisulfite-treated genomic DNA revealed a diminished methylation of uPA promoter in irradiated cells. Transfection with small hairpin RNA (shRNA)-expressing plasmids targeting CpG islands of the uPA promoter showed a marked decline in uPA expression with subsequent decrease in invasion and proliferation of meningioma cells. Further, radiation treatment was found to recruit SP1 transcription factor, which was abrogated by shRNA treatment. Analysis on signaling events demonstrated the activation of MAP kinase kinase (MEK)-extracellular signal-regulated kinase (ERK) in radiation-treated cells, while U0126 (MEK/ERK inhibitor) blocked hypomethylation, recruitment of SP1, and uPA expression. In agreement with our in vitro data, low DNMT1 levels and high uPA were found in intracranial tumors treated with radiation compared to untreated tumors. In conclusion, our data suggest that radiation-mediated hypomethylation triggers uPA expression in meningioma cells.